Spontaneous preterm labour and delivery at under 34 weeks' gestation. Issue 6363 (5th February 1983) - Lamont, R F; Dunlop, P D; Crowley, P; Elder, M G
Abstract : The management and outcome of 242 infants delivered between 26 and 34 weeks' gestation in an obstetrical and neonatal regional referral centre as a result of spontaneous preterm labour were recorded prospectively. Results of the survey show that the decision to intervene and delay delivery will depend on the availability of neonatal intensive care facilities. Infants likely to require intensive neonatal care should be transferred in utero to a centre with these facilities. The use of steroids reduces the mortality of preterm infants. The maximum effect occurs between 30 and 32 weeks' gestation, and there is no benefit after 34 weeks. If the weight is over 1500 g the mode of delivery of the preterm infant presenting by the breech does not influence outcome; if under 1500 g a caesarean section improves survival over those infants born by vaginal breech delivery.